Summertime turbulent heat fluxes at East Antarctica over neighbouring rocky and ice shelf sites - SRIVASTAVA, MANOJ K.; PASRICHA, P. K.; DUTTA, H. N.; SINGH, R. (MAUSAM, 2002)
During the ninth Indian Scientific Expedition to Antarctica, in the year 1990, a micro-meteorological tower was installed at Maitri (70° S, 12° E) on the rocky terrain and on an experimental basis, on the nearby ice-shelf at the location of Dakshin Gangotri (70° 7¢ S, 11° 7¢ E). The synoptic features strongly influencing over the sites are the southeasterly katabatic winds from the polar cap and/or northerly low level warm and humid winds from the sea. These flows are responsible for the formation of strong surface based inversion and strong convective conditions at the ice shelf and rocky terrain during the minimum and maximum insolation periods, respectively. This paper presents a study of surface layer structure over two contrasting surfaces on near-coastal Antarctica and deals with the significance of the energy exchange processes over the rocky Antarctic region and the parameterization of turbulent fluxes over surfaces having strong inversion/convection conditions. The paper makes use of turbulence structure functions which are different from the conventional one given by Panofsky and Dutton (1984).